Early Child Development Outcomes of a Randomized Trial Providing 1 Egg Per Day to Children Age 6 to 15 Months in Malawi. Issue 7 (14th April 2020) - Prado, Elizabeth L; Maleta, Kenneth; Caswell, Bess L; George, Matthews; Oakes, Lisa M; DeBolt, Michaela C; Bragg, Megan G; Arnold, Charles D; Iannotti, Lora L; Lutter, Chessa K; Stewart, Christine P
ABSTRACT: Background: Eggs are a rich source of nutrients important for brain development, including choline, riboflavin, vitamins B-6 and B-12, folate, zinc, protein, and DHA. Objective: Our objective was to evaluate the effect of the consumption of 1 egg per day over a 6-mo period on child development. Methods: In the Mazira Project randomized controlled trial, 660 children aged 6–9 mo were randomly allocated into an intervention or control group. Eggs were provided to intervention households during twice-weekly home visits for 6 mo. Control households were visited at the same frequency. At enrollment, blinded assessors administered the Malawi Developmental Assessment Tool (MDAT), and 2 eye-tracking tasks using a Tobii-Pro X2–60 eye tracker: a visual paired comparison memory task and an Infant Orienting with Attention task. At endline, 6-mo later, blinded assessors administered the MDAT and eye-tracking tasks plus an additional elicited imitation memory task. Results: At endline, intervention and control groups did not significantly differ in any developmental score, with the exception that a smaller percentage of children were delayed in fine motor development in the intervention group (10.6%) compared with the control group (16.5%; prevalence ratio: 0.59, 95% CI: 0.38–0.91). Among 10 prespecified effect modifiers for the 8 primary developmental outcomes, we found 7 significant interactions demonstrating a consistent pattern that children who were less vulnerable, for example, those with higher household wealth and maternal education, showed positive effects of the intervention. Given multiple hypothesis testing, some findings may have been due to chance. Conclusion: The provision of 1 egg per day had no overall effect on child development in this population of children, however, some benefits may be seen among children in less vulnerable circumstances. This trial was registered at clinicaltrials.gov as NCT03385252.